Analyzing Profit Maximization Through Internal Fund Utilization: A Study of Financial Management Practices of Canteen Food Stalls in the Pamantasan ng Lungsod ng Maynila - 4 0 16; 5
Abstract Food stalls in the PLM canteen are essential for students, faculty, and staff, offering both sustenance and entrepreneurial opportunities. However, Canteen stalls face a unique economic environment with limited resources and intense competition, relying solely on internal funds for operations, inventory, overhead, and profit. This study seeks to investigate the strategies and mechanisms employed by canteen food stalls within Pamantasan ng Lungsod ng Maynila to maximize their profits using an internal fund-based capital structure. The study uses non-probabilty sampling with a total of 8 participants using slovin's formula. The study also uses frequency, percentage mean and Spearman's Rho correlation. Data will be gathered through a survey questionnaire that requires thorough procedure planning and instrumentation to ensure accurate and valuable results. The results indicated that 0.915 is the p-value of spearman's rho correlation. This indicates that there is no significant relationship between the respondent's Level of strategies and mechanisms employed in regard to their profit maximization outcomes under an internal fund-based capital structure. This means that the values of strategies and mechanisms employed are not associated with their profit maximization outcomes under an internal fund-based capital structure of the business owners that were operating food stalls within the Pamantasan ng Lungsod ng Maynila. Keywords: Food stalls, Internal-fund based capital structure, Profit.
Business Research: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2